O brother, where art thou? [videorecording (Blu-Ray)] - Coen, Joel; Coen, Ethan; Clooney, George; Turturro, John, 1957-; Nelson, Tim Blake; Durning, Charles, 1923-2012; Goodman, John, 1952-; Hunter, Holly, 1958- (Touchstone Home Entertainment, 2011)
It is the time of the Great Depression, and three escaped convicts embark on an odyssey through the Old South in search of loot stashed at one of their homes. The house is scheduled to be flooded out by a new dam, so time is of the essence.